The effect of mahkota dewa (Phaleria macrocarpa (Scheff) Boerl) leaf etanolic extract on splenic NK 1.1 cells activity - Sofia Mubarika Haryana , Sismindari, Muhammad Ghufron Marsetyawan Soesatyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background : Mahkota dewa (Pheleria macrocarpa (Scheff, Boerl) is an herbal medicine which has been used since many years as traditional medicine in Indonesia against infections.Objective: The study was aimed to know the effect of mahkota dewa extract on cellular immune response, in particular NK1.1 cell activities.Methods: Forty C57BL/6 mice used in this study were divided into 8 groups. In this study, different doses of etanolic extract of mahkota dewa leaf were used i.e. 1.05 mg, 2.1 mg, and 4.2 mg/20g BW. Groups I, II, and III were treated with 1 mg, 2.1 mg, and 4.2 mg/20 g BW of the extract daily for 30 days. In group IV, V, and VI the extract was given simultaneously during 30 days, then the mice were infected with 104 cfu of Listeria monocytogenes (A TCC-191151 for stimulating their immune responses. Whereas group VII was untreated control group, and group VIII received only Listeria monocytogenes. All mice were then sacrificed 48 hours after the last treatment. Splenocyte NK1.1 cells were collected then cultured with YAC-1 (ATCC:TIB 1601 target cells for killing activity assay, expressing NKG2D, CD122 and IFNy assay. Results: The results showed that an oral administration of the extract significantly increased the killing activity of splenic NK 1.1 cell against the target, Y AC-1 cell. Moreover, the extract promoted the secretion of IFN-y from NK1.1 cells, and also induced expression of both surface molecule NKG2D and CD 122. The strongest effect stimulation was on the dosis of 2.1 mg/20 g BW.Conclusion: The extract had effect to augment splenic NK1.1 cell activities, as indicated by increasing their killing activity, expression of surface molecules and IFN-y production.Key words: pha/eria macrocarpa - splenic NK1.1 cell activity - YAC-1 cell - IFNy - NKG2D and CD122 surface molecules